Bahasa Inggris - Muhammad Rafi Siregar; Ahmad Rifai; Mariana; Achmad Manarul (Jurusan Hukum Ekonomi Syariah Fakultas Syariah dan Hukum Uin Alauddin Makassar, 2022)
Abstract Over the past few decades, the financial markets have experienced many long-term crises, causing them to lose the protection of investors' rights. Many parts of the world are looking for ways to trade and communicate with all parties considered, so that their interests are guaranteed to be protected. Muslim people have a hard time investing in the stock market as they feel it does not fit with Sharia law. This paper details three criteria that, if met, would allow Sharia law to invest in the stock market. In this main discussion, the principles outlined provide a better alternative to traditional stock market practices. It was a descriptive study that reviewed the literature, and Sharia law was committed because it is not relevant to the main topic. This article reviews the basic Islamic principles of investing in stock markets and the practices of Islamic tribes worldwide. It looks at Markets and Indices and is intended to guide investors and market authorities looking to learn about the original Sharia judgments regarding investments and benchmark judgments regarding index and mutual fund building. Keywords: Capital market, Islamic stock exchange, Sharia law.